Impact Of Interest Rate Fluctuation On Financial Performance Of Banking Sector In Sri Lanka - Muraleetharan, P. (Eastern University, Sri Lanka and Sri Sathya Sai University For Human Excellence, India, 2025)
Banking sector can be considered as a monopolized segment in the economy. Banks are profit motive and the bank profitability is an important ingredient of financial development through macroeconomic stability. The purpose of this study is to analyze the effect of interest rate fluctuation and performance of banking sector in Sri Lanka. The study conducted to investigate whether there is an impact of deposit interest rate and lending interest rate on the bank’s performance of licensed commercial bank in Sri Lanka. The study considered central bank annual data on the lending interest rate (LR) and deposit interest rate (DR) for the 05-year period from 2019 to 2023. The results show that the interest rate affect on both ROA and ROE in commercial banks. The results obtained from the regression model shows that there is a significant positive and negative relationship financial performance of commercial banks in Sri Lanka. Therefore, the banks should prudently manage their interest rates to improve their financial performance. As well bank must maintain their determinants correctly. There is a limited number of researches regarding this topic in Sri Lankan context and the reason for obtaining the findings of this research is to fill the knowledge gap that existing in current knowledge. This intended to help strategy makers through successfully completion of this investigation.
Keywords: Lending interest rates; Deposit interest rate; Financial performance and ROA